Diabetes mellitus is associated with dry eye syndrome: a meta-analysis - Yoo, Tae Keun; Oh, Ein (International ophthalmology, 2019)
Background Dry eye is the most common eye disorder of tears and ocular surface. However, the extent to which diabetes mellitus may confer risk of dry eye remains uncertain. The aim of this study was to perform a meta-analysis that synthesizes the association between diabetes mellitus and dry eye. Methods Case–control studies were selected from the Medline, Embase, Cochrane database from January 2000 to March 2018. Two reviewers screened potential studies, and eligible studies were included according to keywords and predefined criteria. We calculated the overall risk estimates by using a fixed-effect model or a random-effects model in relation to heterogeneity. Results A total of four studies were included in our meta-analysis consisting of 2,504,794 persons. Our study showed a significant association between diabetes mellitus and the risk of dry eye syndrome (OR 1.30; 95% CI 1.08–1.57; P value = 0.006). However, the heterogeneity was observed ( P value < 0.001, I 2 = 95.2%). Conclusion Our meta-analysis suggests that diabetes mellitus has a significant association with the risk of dry eye. However, this result is limited by heterogeneity. Further prospective and concise studies are needed to confirm the association between diabetes mellitus and dry eye.